Answer:
Step-by-step explanation:
Given:
m∠1 = 65°
Since. ∠1 and ∠2 are the angles of linear pair,
m∠1 + m∠2 = 180°
65° + m∠2 = 180°
m∠2 = 115°
m∠1 = m∠3 [Vertical angles]
m∠3 = 115°
Since, ∠1 and ∠4 is the linear pair of angles,
m∠1 + m∠4 = 180°
65° + m∠4 = 180°
m∠4 = 180 - 65 = 115°
m∠4 + m∠5 = 180° [Consecutive interior angles between the parallel lines]
115° + m∠5 = 180°
m∠5 = 180° - 115° = 65°
m∠5 + m∠6 = 180° [Linear pair of angles]
65° + m∠6 = 180°
m∠6 = 115°
m∠5 = m∠7 [Vertical angles]
m∠5 = m∠7 = 65°
m∠6 = m∠8 [Vertical angles]
m∠6 = m∠8 = 115°